THE INFLUENCE OF LEADERSHIP STYLE AND WORK MOTIVATION ON THE PERFORMANCE OF CONSUMER LENDING UNIT EMPLOYEES AT BANK BTN BEKASI BRANCH OFFICE - Muhamad Fauzil Adzim; Usran Masahere; Fadli Ilyas (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to analyze the influence of leadership style and work motivation on employee performance at the consumer lending unit of Bank BTN Bekasi branch office. The method used in this study is quantitative statistics by distributing questionnaires through Google Forms, the population in this study consisted of 58 employees of the consumer lending unit of Bank BTN Bekasi branch office. Data sources used in this study include primary and secondary data, data processing methods used, descriptive analysis, multiple regression analysis, coefficient of determination and hypothesis testing. Based on the results of the study, it shows that the leadership style variable has a positive influence on employee performance, while work motivation does not affect employee performance. Simultaneously, there is an influence of leadership style and work motivation on employee performance. This is proven based on the calculated F value of 17.066 which means that the calculated F > F table of 3.168 (17.066 > 3.168). In addition, the resulting significance value is 0.000, which is smaller than the significance level of 0.05 (0.000 < 0.05).